Conceptual validation of an innovative remote pulmonary rehabilitation solution for Chronic Obstructive Pulmonary Disease - Méndez, Andrea; Labra, Patricio; Guerrero, Juan Pablo; Nieto, Carlos; Martínez, Bárbara; Hidalgo, Gonzalo; Rodríguez-Núñez, Iván (Canadian Journal of Respiratory Therapy, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of death in the world. Pulmonary rehabilitation (PR) reduces COPD hospitalisations, although its use is low. Telerehabilitation is effective; however, in Chile the development of remote PR technology is incipient. Therefore, the aim of the study was to validate conceptual aspects of an innovative remote PR solution for COPD. This mixed study used a nonprobabilistic sample of PR professionals and people with COPD (PwCOPD) from Santiago. The perception of a conceptual solution for PR through a semi-structured interview was determined. Professionals were also asked about willingness to use technology using a questionnaire designed and validated in 75 professionals in this study. The study was approved by the Ethics Committee and data were collected after informed consent. Twenty-two participants were recruited, of which 14 were professionals and eight were PwCOPD. Among professionals and patients, the willingness to use the solution is positive because it would reduce visits and improve self-management, although it should include a remote/in-person combination, training, and user-friendly interface. Most of the professionals were willing to use technology for pulmonary rehabilitation. The development of telehealth technologies should consider the expectations of patients and professionals and may incorporate elements of persuasive technologies in the design. The results could contribute to the development of digital solutions for remote PR in PwCOPD.